Getting it Right : Strengthening Gender Outcomes in South Sudan - De Silva, Samantha (World Bank, Washington, DC, 2020)
As in most conflicts, in South Sudan, women and girls have been the most vulnerable. Not only do they face many challenges, including extreme poverty and lack of access to basic services and productive assets, but many of the risks they face, such as gender–based violence (GBV), are heightened during times of conflict. The implementation of well–designed and inclusive poverty reduction programs can contribute to empowering women and addressing persistent gender gaps. Yet, until now, there have been few assessments undertaken to better understand how successfully these goals have been achieved. This paper examines how social protection and other poverty reduction programs targeting the most vulnerable have addressed the needs of women and girls in South Sudan. Based on a portfolio review of World Bank operations and a review of impact evaluation evidence, it provides guidance to practitioners to integrate gender equality in the design and implementation of social protection and poverty reduction programs in fragile situations.